The effect of foliar feeding with some nutrients and seaweed extracts on the production of apple trees and the quality of their fruits (Latakia University Journal -Biological Sciences Series, 2025)
This study was carried out in the village of Kassab in Lattakia Governorate on apple trees of the (Golden delicious) variety during the two growing seasons (2021-2022) in order to find out the effect of foliar spraying with some nutrients and seaweed extracts on some physical and chemical specifications of apple fruits Golden delicious the experiment included eight treatments, where spraying with boron, potassium and seaweed extracts was carried out individually or in combination with each other,  The process of spraying with these materials led to a significant superiority of the studied transactions compared to the control, where the average production of trees increased, as the highest value was recorded in the treatment of (K+B + SW) which is (98.17) kg, and the lowest was in the treatment of the witness (68.75) kg, and for the diameter of the fruits, the highest diameter of the fruits was found in the treatment of boron (7.37) cm and the lowest was in the control (6.59) cm, and the highest discoloration of the fruits was found in the treatment (B+K + SW) where it was (87.5) % and the lowest discoloration was found in the control (42.5)%.  As for the hardness of the fruits, the highest value was in the treatment of (SW) (8.77) kg / cm 2 and the lowest value of hardness was in the control (6.22) kg / cm 2, but the dissolved solids did not give significant differences between the coefficients studied.
Keywords: potassium, boron, seaweed extracts, golden delicious, apple.